Affordable High-Resolution LCD 3D Printing via Advanced Ink Formulation for Conventional and Biocompatible Microfluidic Devices - Elfarargy, Reham Gamal (AUC Knowledge Fountain, 2026)
Desktop LCD (MSLA; masked stereolithography) vat photopolymerization offers a globally accessible route for fabricating high-definition microfluidic and biointerface devices. Practical adoption, however, is often constrained by limited optical confinement in commodity water-washable resins and by the scarcity of mechanically compliant, cell-compatible printable formulations for microstructured biological interfaces. This thesis demonstrates an ink/formulation-first strategy to (i) improve voxel confinement in commercial clear resins using accessible photoabsorbers and (ii) engineer a compliant PEGDA–GelMA hydrogel formulation while preserving print fidelity in enclosed and high-aspect-ratio microfeatures. To improve microfluidic print resolution, candidate absorbers were screened by UV–Vis spectroscopy and quantified using Jacob’s working-curve analysis (penetration depth, Dp, and critical dose, Ec) under practical exposure conditions. These tuned resin–absorber combinations enabled reproducible fabrication of embedded circular microchannels with radii down to ~80 µm (e.g., 1.0% w/v curcumin in Anycubic resin) and ~100–140 µm across multiple resin systems (including lower-loading quinoline yellow conditions). Device-level demonstrations included an embedded micromixer printed at ~80% scale, featuring enclosed channels of ~248 × 248 µm² merging into ~720 × 720 µm², and an internal pillar (~162 × 244 µm) spanning the mixing chamber; dye-based visualization showed progressive folding and recombination of streams along the mixer path. A membrane microvalve geometry was also printed, incorporating a ~32 µm thick membrane (~1.4 mm diameter) positioned ~80 µm above a ~400 µm valve seat, with enclosed flow/control conduits retained after post-processing. Additionally, a flexible, biocompatible PEGDA–GelMA ink was developed to remain printable on an LCD platform while providing mechanically compliant microstructures for contractility interfacing, where cell contractility is intended to be quantified through the measurable deformation or displacement of mechanically responsive features (e.g., pillars) under physiologically relevant forces. A baseline PEGDA–GelMA resin was then systematically softened via formulation-level tuning of crosslink density while preserving print fidelity of confined cavities and embedded micropillar arrays; optical/brightfield microscopy confirmed upright pillars with no gross evidence of collapse or fusion (150%-scaled verification; mean column width 152 µm). Mechanical characterization by unconfined compression demonstrated a substantial stiffness reduction from the MPa range (17.6–27.8 MPa) to the kPa range (0.0251 MPa ≈ 25.1 kPa), supporting the design goal of producing deformable microfeatures while maintaining structural stability. Finally, screening-level cytocompatibility (NIH/3T3 fibroblasts) following a multi-day PBS leaching workflow showed cell attachment and spread morphology, supporting progression to future cell application. Overall, these results establish a practical, low-cost workflow for calibrating commercial resins and engineering printable hydrogels to achieve enclosed microfluidics and mechanically relevant microstructures on desktop LCD printers, enabling substantial performance gains through formulation and exposure design rather than hardware upgrades.